Genomic evolution of breast cancer metastasis and relapse. - Yates, LR; Knappskog, S; Wedge, D; Farmery, JHR; Gonzalez, S; Martincorena, I; Alexandrov, LB; Van Loo, P; Haugland, HK; Lilleng, PK; Gundem, G; Gerstung, M; et al. (Elsevier, 2017)
Patterns of genomic evolution between primary and metastatic breast cancer have not been studied in large numbers, despite patients with metastatic breast cancer having dismal survival. We sequenced whole genomes or a panel of 365 genes on 299 samples from 170 patients with locally relapsed or metastatic breast cancer. Several lines of analysis indicate that clones seeding metastasis or relapse disseminate late from primary tumors, but continue to acquire mutations, mostly accessing the same mutational processes active in the primary tumor. Most distant metastases acquired driver mutations not seen in the primary tumor, drawing from a wider repertoire of cancer genes than early drivers. These include a number of clinically actionable alterations and mutations inactivating SWI-SNF and JAK2-STAT3 pathways.